2015
DOI: 10.1007/s10096-015-2399-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of immobilized synthetic anti-lipopolysaccharide peptides for the isolation and detection of bacteria

Abstract: The molecular detection of microorganisms in liquid samples generally requires their enrichment or isolation. The aim of our study was to evaluate the capture and pre-concentration of bacteria by immobilized particular cationic antimicrobial peptides, called synthetic anti-lipopolysaccharide peptides (SALP). For the proof-of-concept and screening of different SALP, the peptides were covalently immobilized on glass slides, and the binding of bacteria was confirmed by microscopic examination of the slides or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For instance, naturally occurring cationic antimicrobial peptides (AMPs) exploit the presence of negatively charged inner core and lipid A of LPS by binding electrostatically and subsequently disrupting the membrane [13][14][15] . Naturally occurring and synthetic surface adsorbing peptides and polymers have been reported to bind LPS specifically to remove LPS and bacteria from solutions [16][17][18] . Other studies have reported LPS crosslinking induced by cationic peptides and polymers, which can lead to the suppression of the endotoxic effect 19-21 . supported symmetric and asymmetric bilayers 9, , and multilayers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, naturally occurring cationic antimicrobial peptides (AMPs) exploit the presence of negatively charged inner core and lipid A of LPS by binding electrostatically and subsequently disrupting the membrane [13][14][15] . Naturally occurring and synthetic surface adsorbing peptides and polymers have been reported to bind LPS specifically to remove LPS and bacteria from solutions [16][17][18] . Other studies have reported LPS crosslinking induced by cationic peptides and polymers, which can lead to the suppression of the endotoxic effect 19-21 . supported symmetric and asymmetric bilayers 9, , and multilayers .…”
Section: Introductionmentioning
confidence: 99%
“…LPS not only serves as a protective coat, but it can also trigger lethal septic shocks when released into bloodstream in a molecular or aggregate form. , Therefore, a number of strategies in the combat against bacteria have targeted LPS. For instance, naturally occurring cationic antimicrobial peptides (AMPs) exploit the presence of negatively charged inner core and lipid A of LPS by binding electrostatically and subsequently disrupting the membrane. Naturally occurring and synthetic surface adsorbing peptides and polymers have been reported to bind LPS specifically to remove LPS and bacteria from solutions. Other studies have reported LPS cross-linking induced by cationic peptides and polymers, which can lead to the suppression of the endotoxic effect. …”
Section: Introductionmentioning
confidence: 99%
“…Lately, it has been reported that this peptide also inhibits activation of the intrinsic coagulation pathway by significantly reducing the activity of Factor XI [67]. Recently, the high binding affinity of Pep19-2.5 towards Gram-positive and Gram-negative bacteria was explored for capturing bacteria in liquid samples [68]. For this, the peptide was immobilized on the surface of carboxylated magnetic beads by carbodiimide crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…With the explosive interest in microbiome effects on human health and the emergence of super bacteria, there are increasing demands for rapid and powerful microorganism analysis techniques. Capturing the dynamic responses of microorganism to environmental changes and stimulus is important for understanding microbial adaption and evolution, which have practical significance in antibiotic drug development and microbiomics study. Conventional biochemical tests of microorganisms are time-consuming, and most techniques are mainly used to study the static states of microorganisms. Because of its high specificity and sensitivity, mass spectrometry is a powerful analytical technique in biochemical analyses, which is widely used in microbiology. Matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) MS is currently the standard method for bacterial identification. , MS imaging is a tool allowing the mapping of biomolecular distributions in biological tissues. MS imaging methods, such as desorption electrospray ionization (DESI), nanoDESI, , MALDI, secondary ion MS (SIMS), and laser ablation electrospray ionization (LAESI) imaging, have also been applied in the studies of microbe-drug interaction, microbial metabolism and communication.…”
mentioning
confidence: 99%